If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
23/3 = x/12 // - x/12
23/3-(x/12) = 0
23/3-1/12*x = 0 // - 23/3
-1/12*x = -23/3 // : -1/12
x = -23/3/(-1/12)
x = 92
x = 92
| (2x-9)/7=5+(x/35) | | 11x-10=67 | | -0.3x^2-0.7x+1.2= | | -(-15)= | | y-(-6)=-14 | | x^5+x+2x^3+9+4x^2= | | (-15)(-8)= | | -3/4+3=8 | | 15+x/6 | | 2x-7/9=4+x/36 | | 8(-15)= | | -3/4x+2=0 | | -15+x/6 | | 5d+10=25+2d | | -18x+3=-25 | | -2b-7-3b=2 | | B=x+xwd | | 7x/12-5=x/4+19 | | 31/3= | | -6j+10=-11-7j | | 5w^3=0 | | b+11=24 | | -6j+10=-11-6j | | .2(3+2x)+1.3x=3.1 | | 5y+x=-30 | | 2n/5-5/11=19/55 | | f(x)=3x^2-9x | | 2x-7=11-2x | | 1/2x+3=-x+12 | | (2x+1)(9x+4)= | | x/6-4=-8 | | 4x+9=4x+13 |